A Systematic Review of Cochlear Implantation in Temporal Bone Fractures and the Significance of Otic Capsule Involvement. Issue 10 (December 2020) - Cowan, Brandon; Oska, Sandra; Arianpour, Khashayar; Svider, Peter F.; Bojrab, Dennis; Hong, Robert S.
Abstract : Objective: Head trauma can cause deafness in cases with and without a skull base fracture. Anatomic disruption can occur with skull base fractures, but inner ear structures can also be damaged by the concussive forces of the trauma even without fracture. It is thought that negative prognostic indicators for successful cochlear implantation (CI) for hearing rehabilitation include fractures involving the otic capsule or ossification of the cochlea. This review evaluates success of CI in posttrauma patients. Data Sources: PubMed/MEDLINE, Cochrane, and Embase. Study Selection: Search terms used were "cochlear implant" AND ("trauma" OR "fracture"). Studies including preoperative computed tomography or magnetic resonance imaging and patient-level outcome data were included. Data Extraction: Study design, perioperative and postoperative outcomes, and complications were reported. Success rates of CI were compared using χ 2 analysis. Data Synthesis: Twenty-three studies encompassing 88 patients who experienced posttraumatic deafness and received subsequent CI were included. CI was reported as successful for 28 of 34 patients (82%) with otic capsule-involving fracture, as compared with 17 of 22 (77%) in those who had an otic capsule-sparing temporal bone fracture, and 15 of 17 (88%) of patients without evidence of fracture (i.e., concussive inner ear injury). Conclusions: In patients with posttraumatic hearing loss, success rates do not significantly differ between cases that do or do not involve fractures of the otic capsule. CI for posttraumatic hearing loss is generally successful.